GROWTH FACTORS FOR THE RHYTHM OF HANDBALL GAME OBJECTIVE PRIORITY FOR NATIONAL HANDBAL TEAM OF SENIORS - Petru Ghervan; Nawarecki Dariusz (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
This material is the result of collaboration readiness of the most representative factors of Romanian Handball Federation and clubs, national team coaches and club teams of seniors, juniors, children, and players with great experience. In total, 165 people were interviewed or responded to questionnaires applied differently for each category during the three years (2008, 2009 and 2010).